Spondylothoracic dysplasia in two siblings - Trindade, C. E. P.; Nóbrega, F. J. de (SAGE Publications, 1977)
The spondylothoracic dysplasia syndrome is characterized by congenital malformations of vertebrae and ribs. As a consequence of the anomalous development of the vertebral column, the neck and thorax are short, and the normal head looks as if emerging from the shoulders. The thorax is short and asymmetric with an increased anteroposterior diameter. Dorsolumbar lordosis and a protuberant abdomen are present. The extremities though normal in length appear long relative to the shortened trunk. Short stature results from the vertebral abnormalities. The syndrome was seen in 2 siblings of nonconsanguineous parents.
Keywords: autosomal recessive inheritance; child; diagnosis; major clinical study; rib malformation; short neck; sibling; spondylothoracic dysplasia; vertebra malformation; Body Height; Case Report; Female; Human; Infant; Male; Neck; Radiography, Thoracic; Ribs; Spine; Syndrome; Thorax